Dual inhibition of atypical PKC signaling and PI3K/Akt signaling dysregulates c-Myc to induce apoptosis in clear cell Renal Cell Carcinoma - Khalid, Khandker Mohammad; Ratnayake, Wishrawana S.; Apostolatos, Christopher A.; Acevedo-Duncan, Mildred (Frontiers in Oncology, 2024)
Renal Cell Carcinoma (RCC) is the most common type of kidney cancer (85%). 75% of the RCC cases involve conventional clear cell RCC (ccRCC). Approximately, 39% of late-stage patients (stage IV) are treated with chemotherapeutic agents. Phosphatidylinositol-3-kinase (PI3K) and Mitogen-Activated Protein Kinase Kinase (MEK)/ extracellular signal-regulated kinase (ERK1/2) pathways are frequently activated in RCC. In addition, atypical PKCs (PKC-ί and PKC ζ) are overexpressed in most cancer cells, and they play a central role in tumor progression and the metastasis of different types of cancers. Our goal is to establish the role of aPKCs in the regulation of multiple key activated pathways in ccRCC. In this study, we also established a novel therapeutic regimen for dual inhibition of key activated pathways.In this study, 786-0 and Caki-1 cells were studied and subjected to cell viability assay, western blot analysis, scratch & wound healing assay, transwell invasion assay, immunofluorescence, immunoprecipitation, flow cytometry, and quantitative real-time polymerase chain reaction. We used combination of PI3K inhibitor-Alpelisib (BYL719) and ICA-1 (a PKC-ι-specific 5-amino-1-2,3-dihydroxy-4-(methylcyclopentyl)-1H-imidazole-4-carboxamide). In addition to drug treatment, small interfering RNA (siRNA) technology was used to further confirm the experimental outcome of the drug treatment.Our results suggest that treatment of ccRCC cells with a combination of ICA-1 (aPKC inhibitor) and BYL719 (PI3K inhibitor) downregulates PKC-ί and causes downstream inhibition of c-Myc.Inhibition of the PKCί also reduces activation of MEK/ERK1/2. It is observed that treatment with ICA-1 disrupts the level of the aPKC-Akt1 association. ICA-1 treatment also shows a reduced level of association between aPKC and c-Myc. The inhibition of aPKCs and downstream effector proteins by combination therapy is more pronounced compared to a single therapy. These effects contribute to reduced cell growth, and eventually, the induction of apoptosis. The decreased level of N-cadherin, p-vimentin, and vimentin and the increased level of E-cadherin confirm reduced malignancy.Therefore, implementing a combination of Alpelisib and a PKC- inhibitor is an effective approach to reducing cell proliferation, and invasion that eventually induces apoptosis and may be considered as a potential therapeutic option in ccRCC.